2020
DOI: 10.3389/fcell.2020.00753
|View full text |Cite|
|
Sign up to set email alerts
|

eIF3a Regulation of NHEJ Repair Protein Synthesis and Cellular Response to Ionizing Radiation

Abstract: Translation initiation in protein synthesis regulated by eukaryotic initiation factors (eIFs) is a crucial step in controlling gene expression. eIF3a has been shown to regulate protein synthesis and cellular response to treatments by anticancer agents including cisplatin by regulating nucleotide excision repair. In this study, we tested the hypothesis that eIF3a regulates the synthesis of proteins important for the repair of double-strand DNA breaks induced by ionizing radiation (IR). We found that eIF3a upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Although mTORC2 is known to phosphorylate Akt at Ser 473 43 , we did not find any effect of eIF3a knockdown on the expression of Rictor (unpublished observation), a key component of mTORC2 44 . Although this finding does not rule out the possible involvement of mTORC2 in mediating eIF3a regulation of Akt, it has been shown previously that eIF3a suppresses the synthesis of DNA-PKcs 7 , 8 , which is known to activate and phosphorylate Akt 45 , 46 . Thus, it is tempting to speculate that DNA-PKcs may mediate eIF3a regulation of Akt phosphorylation and activation.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Although mTORC2 is known to phosphorylate Akt at Ser 473 43 , we did not find any effect of eIF3a knockdown on the expression of Rictor (unpublished observation), a key component of mTORC2 44 . Although this finding does not rule out the possible involvement of mTORC2 in mediating eIF3a regulation of Akt, it has been shown previously that eIF3a suppresses the synthesis of DNA-PKcs 7 , 8 , which is known to activate and phosphorylate Akt 45 , 46 . Thus, it is tempting to speculate that DNA-PKcs may mediate eIF3a regulation of Akt phosphorylation and activation.…”
Section: Discussioncontrasting
confidence: 62%
“…The biological significances of eIF3a in cancer disease have also been recognized, including tumorigenesis 3 and prognosis 4 . eIF3a has been shown to cause cellular sensitivity to DNA-damaging treatments including cisplatin 5 , 6 , doxorubicin 5 , 7 and ionizing radiation 8 , which may contribute to tumorigenesis and prognosis. These observations have been ascribed to the non-canonical function of eIF3a in suppressing synthesis of DNA repair proteins important for nucleotide excision repair (NER) of DNA crosslink adducts induced by cisplatin 5 , 6 and for non-homologous end joining (NHEJ) repair of double strand DNA breaks induced by doxorubicin and radiation 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As a key regulator in cancer, eIF3a is expressed at high levels in multiple cancers and is relevant to the sensitivity of DNA damage-induced therapy, such as platinum agents and ionizing radiation (Tumia et al, 2020). As shown in our previous study, eIF3a increases the sensitivity of ovarian cancer and non-small cell lung cancer to platinum-based chemotherapy, and the patients with a high level of eIF3a have a better prognosis (Yin et al, 2011b;.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies, including our own study, supported the hypothesis that eIF3a knockdown reduces the cellular response to cisplatin by regulating the expression of DNA repair proteins in lung cancer (Yin et al, 2011a), nasopharyngeal carcinoma (Liu et al, 2011), and ovarian cancer . Tumia R et al also reported that high eIF3a expression increases radiotherapy and chemotherapy responses in patients with breast, gastric, lung, and ovarian cancer (Tumia et al, 2020), further suggesting that eIF3a may affect patient responses to treatments.…”
Section: Introductionmentioning
confidence: 97%
“…It has also been shown to associate with cancer prognosis and patient response to chemotherapy ( 11 , 12 , 13 ) and to regulate cancer cell proliferation ( 14 , 15 , 16 , 17 ). Although the eIF3a function in cancer prognosis has been shown to attribute to its function in suppressing synthesis of DNA damage repair proteins in cellular response to DNA-damaging drugs and radiation ( 11 , 18 , 19 ), it remains to be determined how eIF3a controls cancer cell proliferation.…”
mentioning
confidence: 99%